Gender health care inequalities in health crisis: when uncertainty can lead to inequality - Isabel Aguilar-Palacio; Blanca Obón-Azuara; Sara Castel-Feced; Sara Malo; Julia Teresa; María José Rabanaque (Archives of Public Health, 2024)
Abstract Background In health crisis, inequalities in access to and use of health care services become more evident. The objective of this study is to analyse the existence and evolution of gender inequalities in access to and use of healthcare services in the context of the COVID-19 health crisis. Methods Retrospective cohort study using data from all individuals with a confirmed COVID-19 infection from March 2020 to March 2022 in Aragón (Spain) (390,099 cases). Health care access and use was analysed by gender for the different pandemic waves. Univariate and multivariate analyses were conducted to evaluate the effect of sex in health care. Blinder-Oaxaca decomposition methods were performed to explain gender gaps observed. Results The health care received throughout the COVID-19 pandemic differed between men and women. Women were admitted to hospital and intensive care units less frequently than men and their stays were shorter. Differences observed between men and women narrowed throughout the pandemic, but persisted even after adjusting for age, socioeconomic status, morbidity burden or the patient's place of residence. Differences in sociodemographic characteristics and morbidity burden could explain partially the gender inequalities found, mainly in the later phases of the pandemic, but not in the earlier waves. Conclusions There were gender inequalities in access to and use of health services during the COVID-19 pandemic. Inequalities were greater in the first waves of the pandemic, but did not disappear. Analysis of health crises must take into account an intersectional gender perspective to ensure equitable health care.